Print and politics in the East Midlands constituencies c.1790-1832 - Nicholson, Hannah (2019)
This thesis is an examination of printed political ephemera, produced and distributed during election canvasses between 1790 and 1832. Previous studies have highlighted the popular, public nature of election rituals during the late eighteenth and early nineteenth centuries, although, to date, few have fully appreciated the level and range of printed literature produced during the course of canvassing. This thesis uses a broad range of printed and manuscript evidence including political ephemera, local newspapers, election receipts, and correspondences from borough and county elections, highlighting the level of work which went into orchestrating a canvass in the unreformed era, especially by candidates, their political agents, and printers. The focus of this study is the borough and county constituencies of Derbyshire, Leicestershire, and Nottinghamshire, with particular emphasis on borough elections. Between 1790 and 1832, this region, along with the rest of the country, underwent profound social and political change, and so this thesis not only acts as an important test case for the operation of local political culture nationally, but also represents the first comprehensive study of printed electoral culture for the region.